2018
DOI: 10.1002/cam4.1627
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differential expressed lncRNAs in human thyroid cancer by a genome‐wide analyses

Abstract: Recently, a growing number of evidence has revealed that long noncoding RNAs (lncRNAs) act as key regulators in various cellular biologic processes, and dysregulation of lncRNAs involves in tumorigenesis and cancer progression. However, the expression pattern, clinical relevance, and biologic function of most lncRNAs in human thyroid cancer remain unclear. To identify more thyroid‐cancer‐associated lncRNAs, we analyzed the expression profile of lncRNAs in thyroid cancer tissues and adjacent normal or non‐tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…For example, a bioinformatics analysis study showed that FAM95B1 and UCA1 were correlated with cervical lymph node metastasis, tumor staging, and TC prognosis. Lu et al reported that the dysregulation of RUNDC3A-AS1, FOXD-AS1, RUNDC3A-AS1 and FOXD-AS1 was correlated to a shorter overall survival time in patients with TC [25]. However, only a small part of lncRNAs were reported in TC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a bioinformatics analysis study showed that FAM95B1 and UCA1 were correlated with cervical lymph node metastasis, tumor staging, and TC prognosis. Lu et al reported that the dysregulation of RUNDC3A-AS1, FOXD-AS1, RUNDC3A-AS1 and FOXD-AS1 was correlated to a shorter overall survival time in patients with TC [25]. However, only a small part of lncRNAs were reported in TC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations showed that LINC01354 participates in TP53 signaling pathways via hsa‐mir‐107 and hsa‐mir‐497‐5p in colorectal cancer, regulating CDK6 and CCNE1 , respectively . Notably, it was recently reported that LINC01354 dysregulation is related to genomic alterations in thyroid cancer . The results of this study show that LINC01354 is also a noncoding gene involved in the genesis of HNSCC, and its role in the regulation of tumorigenesis and development deserves further exploration.…”
Section: Discussionmentioning
confidence: 52%
“…transcribed from UNC5B is a newly confirmed lncRNA in thyroid cancer [26]. UNC5B-AS1 is 652 nucleotides in length, containing 2 exons and located in the genome 10q22.1 [27].…”
Section: Discussionmentioning
confidence: 99%